2021
DOI: 10.1021/acs.biochem.1c00512
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Nitro-Forming Enzyme Involved in Fosfazinomycin Biosynthesis

Abstract: N-hydroxylating monooxygenases (NMOs) are a subclass of flavindependent enzymes that hydroxylate nitrogen atoms. Recently, unique NMOs that perform multiple reactions on one substrate molecule have been identified. Fosfazinomycin M (FzmM) is one such NMO, forming nitrosuccinate from aspartate (Asp) in the fosfazinomycin biosynthetic pathway in some Streptomyces sp. This work details the biochemical and kinetic analysis of FzmM. Steady-state kinetic investigation shows that FzmM performs a coupled reaction with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 54 publications
6
15
0
Order By: Relevance
“…Overall, these kinetics and spectral properties closely resemble those originally described for FzmM from Streptomyces sp. XY332 ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, these kinetics and spectral properties closely resemble those originally described for FzmM from Streptomyces sp. XY332 ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…These initial findings have been followed by an increasing interest in NMOs and many enzymes belonging to this family have been discovered in the past years ( 19 , 20 ). A subgroup of NMOs that are attracting considerable interest are PcXL, FzmM, and its homolog CreE ( 21 , 22 , 23 , 24 , 25 , 26 ). They were isolated from Streptomyces species and reported to participate in the biosynthesis of phosphonocystoximate, fosfazinomycin, and cremeomycin, respectively.…”
mentioning
confidence: 99%
“…A k cat of 4.28 � 0.07 s À 1 and a K M of 0.82 � 0.06 mM were measured with L-aspartate, which are similar to previously reported values for homologous enzymes (Figure 1 & Table 1). [13,17] We observed little change on the k cat value with D-aspartate but noted a ~23-fold increase in the K M value, suggesting that CreE preferentially binds Laspartate (Figure 1 & Table 1). A previous report showed that SV2À NMO was not active with D-aspartate by monitoring the rate of NADPH oxidation.…”
Section: Steady-state Kinetic Analysismentioning
confidence: 88%
“…[11,16] However, CreE is an unusual member of this subclass, because the enzyme catalyzes three sequential hydroxylation reactions of L-aspartate to yield nitrosuccinate, in contrast to the typical single oxidation reaction of NMOs (Scheme 1B). [8,11,13,17] Here we present the kinetic characterization of CreE. Steady-state kinetic studies demonstrated that CreE is stereospecific for L-aspartate and that the oxidation is highly coupled.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation